2019
DOI: 10.1093/mnrasl/slz139
|View full text |Cite
|
Sign up to set email alerts
|

Group pre-processing versus cluster ram-pressure stripping: the case of ESO156−G029

Abstract: We report on observations of ESO156-G029, member of a galaxy group which is positioned at the virial radius of cluster Abell 3193. ESO156-G029 is located ∼ 1.4 Mpc in projected distance from the brightest cluster galaxy NGC1500. We show that ESO156-G029 has disturbed gas kinematics and a highly asymmetric neutral hydrogen (H i) distribution, which are consequences of group pre-processing, and possibly of rampressure. Based on the current data we propose a scenario in which ESO156-G029 had a minor gas-rich merg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…These groups are: J0258-74, J1026-19, J1250-20, J1408-21 and J1956-50. The only exception to these scenarios is the J0400-52 group as it is infalling into a cluster Džudžar et al (2019b). The rapid H i-removal process, ram-pressure, is expected in the S1 galaxy within J0400-52 once it approaches the cluster centre Džudžar et al (2019b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These groups are: J0258-74, J1026-19, J1250-20, J1408-21 and J1956-50. The only exception to these scenarios is the J0400-52 group as it is infalling into a cluster Džudžar et al (2019b). The rapid H i-removal process, ram-pressure, is expected in the S1 galaxy within J0400-52 once it approaches the cluster centre Džudžar et al (2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, each of these galaxies have a peculiar morphology that can be connected with an interaction and possible accretion of the H i gas. J0400-51:S1 has visible faint stellar streams in the North, and we discussed in Džudžar et al (2019b) how these may be related to a merger. J1250-20:S1 had clear ongoing multiple interactions and a stellar stream reaching out of a spiral arm (Džudžar et al 2019a) and see Figure H4.…”
Section: H I Distribution In Galaxiesmentioning
confidence: 99%
See 2 more Smart Citations
“…McGee et al 2009(see, e.q. McGee et al , 2014Aragon Calvo et al 2019;Džudžar et al 2019, and references therein). Alpaslan et al (2016) found that among spiral galaxies in GAMA fields galaxies which lie closer to the filament axes have higher stellar masses and higher star-formation rates than spiral galaxies in the outer parts of filaments.…”
Section: Galaxy Evolution In the Supercluster And In The Cocoonmentioning
confidence: 99%